Physiotherapy Management In Bilateral Knee Osteoarthritis By Providing Manual Therapy And Exercise Therapy: Case Report - Hidayah, Fenisa Nurul; Naufal, Adnan Faris; Pradana, Anas (Universitas Muhammadiyah Surakarta, 2023)
Osteoarthritis of the knee is a degenerative disease that occurs in the joints and is progressive in nature which is characterized by damage to the cartilage structure which causes pathological changes in the joints. Symptoms that often arise are stiffness in the morning and there is also a